Elections and Political Organizations in the 19th Century in Central America: A Historiographic Approach - Avendaño Rojas, Xiomara (2021)
The political history of Central America focuses on conflicts between elites, memories and apologetic biographies about politicians, rulers or military men. A review of the electoral experience of Guatemala, Costa Rica, Nicaragua, Honduras and El Salvador in the 19th century brings to light a still incipient historiographical renewal. The text summarizes the organization and implementation of indirect elections, observing the normative changes and the political practice initiated since the crisis of the Spanish monarchy (1810-1812). In addition, it raises some changes throughout the 19th century such as the following:  the gradual elimination of levels of election, the introduction of census suffrage, the evolution from factions to the formation of the political party; finally, new questions about some issues to deepen are exposed. A result to be highlighted is that access to power by means of coups d'état did not annul the right to suffrage or the participation of diverse social sectors in the elections. Studies of the electoral process need to go beyond the national vision in order to have more arguments for a comparative analysis of the formation of the representative system in Central America.